Advances in Olefin Metathesis: Water Sensitivity and Catalyst Synthesis - Botti, Adrian (Université d'Ottawa / University of Ottawa, 2016)
Olefin metathesis is the most powerful, versatile reaction in current use for the formation of new carbon-carbon bonds. While metathesis has been known for over 60 years, it has only recently been implemented into pharmaceutical and specialty chemical manufacturing. The slow uptake of olefin metathesis can be attributed in part to low catalyst productivity, a consequence of short catalyst lifetime. Improving catalyst activity is critical for the advancement of metathesis. This improvement can be achieved through greater understanding of the catalysts and their limitations. The ability to perform metathesis in aqueous media is desirable, but as yet largely unrealized, for the modification of water-soluble, biologically-relevant substrates. At present, high catalyst loadings are necessary even for less demanding metathesis reactions in water. The limited mutual solubility of the catalyst and substrate in water are one limitation. Examined in this thesis are more fundamental challenges associated with catalyst deactivation by water. The impact of water on catalyst productivity was assessed for both the second-generation Grubbs catalyst GII, and the phosphine-free Hoveyda catalyst HII, in ring-closing and cross-metathesis reactions. Water was shown to have a negative impact on metathesis productivity, owing to catalyst decomposition. The decomposition pathway was catalyst-dependent: GII was found to decompose through a pathway in which water accelerated abstraction of the methylidene ligand by dissociated phosphine. For HII, water was found to decompose the metallacyclobutane intermediate. A β-hydride transfer mechanism was proposed, to account for the organic decomposition products observed. Chapter 4 focuses on problems encountered during the synthesis of ruthenium catalysts, and presents improved methods. An updated method was developed for the synthesis of phenyldiazomethane, the principal source of the alkylidene ligand required in synthesis of GI. Challenges in use of the phosphine-scavenging resin Amberlyst-15 resin are discussed. Improving synthetic routes to the important first- and second-generation Grubbs catalysts will aid in expansion of olefin metathesis methodologies, particularly in the industrial context, in which batch-to-batch reproducibility is paramount.
Keywords: Olefin Metathesis; Organometallic Chemistry; Catalysis; Water Sensitivity